Uncommon ossicle in Holothuria (Mertensiothuria) leucospilota from Teluk Nipah, Pangkor Island - Kamarudin, Kamarul Rahim; Muhd Lutfi, Fatin Najihah; Che Zahri, Mohd Zulhafiz; Mohamed Reha, Maryam (USIM, 2018)
The high popularity of a commercial sea cucumber species on Pangkor Island (i.e. Stichopus horrens) has resulted in a lack of studies on Holothuria (Mertensiothuria) leucospilota from Pangkor Island, Perak, Malaysia. S. horrens is the main ingredient of gamat-based traditional medicine on the resort island, while H. leucospilota is the most dominant species. For that reason, this study aimed to isolate ossicles from a specimen of morphospecies H. leucospilota collected from Teluk Nipah Beach, Pangkor Island; and to determine the shapes of the ossicles for species verification. A number of six ossicle shapes were observed. Beside buttons and tables as the common ossicle shapes; I-shaped rod, long I-shaped rod, branched rod, and spider-shaped rod were also documented. Nonetheless, the spider-shaped rod is an unusual ossicle shape in H. leucospilota as there was no previous record on it, thus it could be considered as a new finding. In summary, the results of this research indicate the uniqueness of the specimen of morphospecies H. leucospilota as a result of the presence of the spider-shaped rod. More studies with more samples, more morphological approaches as well as more molecular techniques need to be incorporated in future for a better insight.